(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study investigates the effect of chamber corner fillet geometry on the wave energy capture performance of an L-shaped Oscillating Water Column (L-OWC) device. Numerical simulations were conducted in FLOW-3D at a 1:20 scale, using representative wave conditions from Northeastern Taiwan, to evaluate the energy conversion efficiency of breakwater-integrated OWCs under various wave periods. The analysis focuses on the effect of varying corner fillet dimensions at three key locations of the L-OWC: the water inlet fillet (LR1), the upper chamber fillet (LR2), and the bottom chamber fillet (LR3). To optimize energy capture, the Impeller Model in FLOW-3D was employed, with systematic adjustment of the accommodation coefficient for rotational velocity (Ad) to determine the optimal Power Take-Off (PTO) damping coefficient. Simulation results indicate that the filleted L-OWC model achieved a 16.1% increase in capture factor compared to the baseline configuration (model without fillet). The optimal corner fillet radii were identified as 180 mm for LR1, 90 mm for LR2, and 90 mm for LR3. The introduction of corner fillets was found to enhance internal flow velocity, increase volumetric airflow, and improve water level oscillations, thereby significantly improving the system’s energy capture efficiency.